How lecturers integrate computer-related technology into instructional practice: a qualitative study at a higher learning institution in Malaysia - Bashir, Kishabale; Omar Malacela, Issa; Syed Hassan, Sharifah Sariah (IIUM Press, 2017)
Malaysian higher learning institutions have embraced the 21st century skills in teaching and learning to ensure career readiness among learners. Information Communication Technology tools provide the opportunity for educators to apply problemsolving and project-based learning in both face-to-face and blended learning. However, there have been issues with educators’ awareness and skills in utilizing the technology tools in the instructional processes. This study attempted to explore the experiences and intentions of lecturers to integrate computer-related technologies in undergraduate classrooms. In-depth semi-structured interviews were conducted with three lecturers, two of them teach foreign languages and the other teaches Instructional Technology. The study sought to reveal the pedagogical approach and types of information technology adopted in the classrooms. This study addressed teachers’ awareness the use of technology in the classroom and issues related to it. The results were thematized based on Web 2.0 tools integration, pedagogical approach in addressing higher order thinking skills and student career readiness. Lecturers were found to be aware of the relevance of Web 2.0 tools for instructional purposes. However, they highlighted low Internet speed as the main challenge in their efforts to integrate technology into their instructional activities. This research contributes to the area of TPACK (Technology Pedagogical Content Knowledge) by highlighting the application of computer-related technologies into classroom instruction. It also highlights how such technologies are matched with learner-centered instructional strategies to enhance learners’ 21st century skills that are essential for career readiness.